The Cyclical Nature of Market Economy Development: A ‎Model-Based Analysis - Yan, Chaoheng; Wang, Xianpeng; Wang, Kexin; Gu, Yuhao; Nella , Zhudro (International Journal of Accounting and Economics Studies, 2025)
This paper delves into the cyclical nature of market economy development. By presenting a simple multiplier-accelerator model, it illustrates the intrinsic mechanisms underlying economic cycles. The study reviews major ‎economic cycle typologies, including Kitchin, Juglar, Kuznets, and Kondratieff cycles, and analyzes how ‎internal factors (investment behavior, consumption patterns) and external factors (technological innovations, ‎international trade) jointly shape these cycles. Empirical data from the United States, Germany, and global ‎aggregates are used to validate cyclical patterns, with a specific focus on GDP growth rates and industrial ‎production indices. The paper concludes with implications for policymakers, businesses, and investors, ‎highlighting the value of cycle awareness for evidence-based decision-making‎.
Keywords: Economic Cycles; Cycle Typologies; Macroeconomic Indicators; Econometric Methods; Globalization & Cycle ‎Synchronization